2007
DOI: 10.1080/00071660701247814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of feeding 2-hydroxy-4-(methylthio)butanoic acid andDL-methionine supplemented maize–soybean–rapeseed meal diets on growth performance and carcase quality of broilers

Abstract: 1. This experiment was conducted to compare the effectiveness of DL-2-hydroxy-4-(methylthio)butanoic acid (HMTBA) and DL-methionine (DLM) on growth performance and carcase quality of broilers in a 2 x 3 x 2 factorial experimental design including two methionine (Met) sources, three equimolar levels of Met supplementation and two sexes. 2. No difference was observed between the two Met sources in growth performance and muscle deposition from 10 to 49 d. With increasing Met levels, average daily gain was increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
5
8
0
1
Order By: Relevance
“…Notably, the higher BW of chickens supplemented with DL-HMB was accompanied by higher levels of plasma insulin-like growth factor-I, a potent anabolic hormone in chickens, (Willemsen et al, 2011), a finding that could help to explain the greater WG observed with the graded inclusion of ALIMET ® in broiler chicken diets. There are no difference between sources and level of Met on the performance of broilers (Dibner, 2003;Dibner et al, 2004;Liu et al, 2007;Abdel-Maksoud et al, 2010) and the supplementation of broiler diets with dry DL-Met or liquid HMB had no effect on FCR (Motl et al, 2005), a finding that is in agreement with the current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, the higher BW of chickens supplemented with DL-HMB was accompanied by higher levels of plasma insulin-like growth factor-I, a potent anabolic hormone in chickens, (Willemsen et al, 2011), a finding that could help to explain the greater WG observed with the graded inclusion of ALIMET ® in broiler chicken diets. There are no difference between sources and level of Met on the performance of broilers (Dibner, 2003;Dibner et al, 2004;Liu et al, 2007;Abdel-Maksoud et al, 2010) and the supplementation of broiler diets with dry DL-Met or liquid HMB had no effect on FCR (Motl et al, 2005), a finding that is in agreement with the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have reported equivalent performance of broilers supplemented with DL-Met and DL-HMB on equimolar basis in the diets (Knight and Dibner, 1984;Garlich, 1985;Romer and Abel, 1999). However, there is conflict results in the last decade concerning the relative bioefficacy between DL-Met and DL-HMB in commercial broilers (Lemme et al, 2002;Daenner and Bessei, 2003;Dibner, 2003;Drew et al, 2003;Meirelles et al, 2003;Dibner et al, 2004;Motl et al, 2005;Liu et al, 2006;Vazquez-Anon et al, 2006a;Liu et al, 2007;Saki et al, 2011). Investigate of relative bioefficacy between synthetic Met sources and their effect on broiler performance is main focus of studies.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the carcass organs were in agreement with the other researchers' results (Liu et al, 2007;Hussein et al, 2019Hussein et al, , 2020. Farran et al (2010) reported that the muscle weights were not affected by the inclusion of enzyme preparations.…”
Section: Discussionsupporting
confidence: 91%
“…In trials where methionine was supplemented to protein-deficient diets, some researchers also observed the same molar bio-efficacy for growth performance and carcass quality between HMTBA and DL-Met (50). This may be due to the different TSAA levels in the trial diets.…”
Section: The Bio-efficacy Of L-met Dl-met and Hmtba In Poultrymentioning
confidence: 90%
“…This may be due to the different TSAA levels in the trial diets. Even though HMTBA showed similar effects to DL-Met on body weight gain, feed efficiency and muscle deposition, Liu et al reported superior breast and thigh muscle color in HMTBA-fed birds compared to DL-Met-fed birds (50).…”
Section: The Bio-efficacy Of L-met Dl-met and Hmtba In Poultrymentioning
confidence: 97%